Analisis Kinerja Keuangan Pt. Aneka Tambang (Persero) Tbk Yang Terdaftar Di Bursa Efek Indonesia Tahun 2011-2015 - Aryani, Valeria Deti, Jati Waskito, S.E., M.Si (2017)
This study aims to determine the company's performance analysis Aneka Tambang (Persero) Tbk. 2011-2015. The data used is secondary data obtained through an annual financial report issued by the Indonesia Stock Exchange. In this study does not use the sample, due to the nature of this research is a case study so that the data obtained from only one company, PT Aneka Tambang (Persero) is listed on the Indonesia Stock Exchange. This study uses quantitative data obtained shall be formulated and then analyzed based on the theories that are relevant to the issues in order to draw conclusions and suggestions. In this case the data obtained were analyzed using methods of financial reports by comparing the ratio of the average internal rate financial statements. Aneka Tambang (Persero) Tbk 2011sampai year 2015 financial performance at PT. Aneka Tambang in the last five years. Judging from the analysis of four financial ratio is the ratio of liquidity, activity, profitability and solvency show that the performance is quite good, because the company is able to show a large ratio in accordance with the minimum standards set.